Optimasi Waktu Reaksi dan pH terhadap Peningkatan Yield Eco Enzyme - Teodora Dasilva; Syntia Nabila; Mega Kasmiyatun; Ery Fatarina Purwaningtyas; Priyono Kusumo (Jurnal Sains dan Teknologi, 2024)
Eco enzyme is a biocatalyst obtained from a fermentation process involving microorganisms, and has the potential to be applied in various environmental and industrial fields. This research aims to determine the optimum conditions for the volume of eco enzyme, determine the most influential variables between time and pH used during the eco enzyme fermentation process and the chemical characteristics of the eco enzyme product which was fermented for three months. Optimization method using the Central Composite Design – Response Surface Methodology (RSM) method. The comparison made in eco enzyme fermentation is water: organic waste: molasses = 10: 3: 1 = 5000 ml: 1500 gr: 500 gr. Fermentation for 3 months resulted in optimum conditions for making eco enzyme found at a reaction time of 96.213 and a pH of 5.207, with a maximum % yield of 10.24. The most influential variable in this research is pH. FTIR test results show the strongest absorption in the -OH (hydroxyl) group with alcohol properties at a wavelength of 3307.99 cm⁻¹, with a low transmittance of 48.2%. This group has antimicrobial properties that support the growth of good bacteria and other microbes.